Comics in the Anthropocene: Graphic Narratives of Apocalypse, Regeneration and Warning - Olsza, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2022)
Narratives of the Anthropocene function in the realm of not only scientific but also popular discourses. Indeed, the most popular narratives of the Anthropocene, namely the story of the apocalypse and the story of progress, with their respective temporalities, are particularly well-represented in comics. The present article looks at the Anthropocene through the lenses of word and image, tracing the response of the medium of comics to the ongoing catastrophe, including Joe Sacco’s Paying the Land (2020), Scott Snyder and Yanick Paquette’s modern take on Swamp Thing (2019) and Richard McGuire’s Here (2014). Paying the Land is a story of the Dene people and their response to the Anthropocene. Drawing on the opposition between nature and progress, it examines whether empathy can stop capitalistic exploitation of Indigenous communities and the land which they cherish. Swamp Thing, seemingly a narrative of environmental apocalypse, also functions as a story of ecological reconciliation and regeneration. Finally, Here builds on and deconstructs the narrative of progress, demonstrating how a specific location has and will be transformed from 3,000,500,000 BCE to 22,175 CE, offering the reader/viewer a non-chronological look at environmental changes. Apart from the visions of the now and the future that these graphic narratives present, temporality coded in their “grammar” (layout, panels and gutters) is also discussed.